Food and medicine homology: a potential nutritional intervention strategy for post-acute COVID-19 syndrome - Li, Zhan; Liu, Yingqi; Ding, Wei; Liu, Yue; Li, Wang; Guan, Shanshan; Liu, Xianjun; Wang, Guizhen; Liu, Qiong; Jiang, Chunwa; Peng, Xinli; Li, Hao; et al. (Frontiers in Pharmacology, 2025)
After recovering from severe acute respiratory syndrome of coronavirus 2 (SARS-CoV-2) acute infection, some patients with corona virus disease 2019 (COVID-19) still are affected by post-acute COVID-19 syndrome (PACS). Traditional Chinese medicine (TCM) has played an important role in the recovery period of COVID-19. As a unique type of Chinese botanical drugs, foods with property of food and medicine homology (FMH) has the dual characteristics of drug and food, which has advantages over usual drugs in safety and daily application. This review analyzed a total of 290 peer-reviewed publications on the progress of dozens of formulas and single botanical drugs, which were systematically collected from the electronic scientific databases, including PubMed, Web of Science, and China National Knowledge Infrastructure (CNKI), as well as other literature sources, such as classic Chinese medicine books. The symptoms of PACS and the advancements in the application of FMH foods in PACS intervention are summarized, and the challenges in the regulatory characteristics and food safety are further discussed. It is expected that the application of FMH foods would bring new opportunity for the treatment and daily intervention of PACS, and this review provides a foundation for the development of PACS intervention foods.